CONFUCIANISM DOCTRINE AND ITS/CHINESE NATIONAL RELIGION ROTATION PROCESSES - Ruziyev Alisher Kholmurodovich (Modern American Journals, 2025)
In this articleIn ancient China, two religions emerged, between which there was a significant difference: Confucianism, which was a morally oriented teaching, and Daoism, which was inclined to mysticism. The founder of Confucianism (the Chinese name is "zhu Jia Xue sho" - the teaching of the school of intellectual scholars) was the famous thinker of ancient China, Kun-Tzu (teacher of the day), or Confucius (551– 479 BC). Therefore, in this article, Confucianism will be analyzed together.
Keywords: Confucianism, religion, Heaven worship, justice, ancestor worship, Taoism.